"Syunk – the Sun, Iki – the Moon": From Folklore Tales to Telegram-Based Language Education and Cultural Learning of the Khanty Language - Sugyan Anna; Andreeva Alina; Satvalova Elena; Kolmogorova Anastasiya (Виртуальная коммуникация и социальные сети)
Digital technologies, in particular, chatbots, can revitalize indigenous languages. In this research, a chatbot was used as a digital tool to teach the Khanty language spoken in Russian North. A bibliometric analysis based on the R language revealed the relevance of this approach for other multilingual communities worldwide. Today, the Khanty language is revitalized in such projects as Language Nests and Nomadic Schools and Kindergartens. The authors developed a draft product for teaching Khanty as part of family education. Though addressed mainly to children, it can help parents who would like to remember their native language while encouraging their children to learn their native culture. Using game mechanics, people can listen to or read Khanty fairy tales in Russian and in the Kazym dialect of the Khanty language, do vocabulary and grammar exercises, and find out about Khanty traditions and rituals. Telegram bots have a great potential for preserving and popularizing indigenous languages in the context of social globalization and digitalization.